Implementasi High Availability Web Server pada Cloud Computing Menggunakan Pacemaker - Nurul Diana S; Rahmat Suhatman; Istianah Muslim (UIN Sultan Syarif Kasim Riau, 2018)
Information and communication become one of the most important needs for everyday life. Because of the increasing demand for information that can be accessed in various media, it requires a reliable design to be able to provide the best service to the client, although the demand and server load increasingly in line with the increasing demand of the client. If using a single server that serves client requests, of course this can not be said reliable because it could be a time the server will experience downtime and can not serve client requests. To overcome this problem applied high availability methods using pacemaker tools that provide high availability for the server so that if one server dies then there is another server that takes over the function of the server. Further data replication techniques used to replicate data between servers with other servers using glusterfs tools. The results show that when failover takes 3.8 seconds for node 2 to take over the function of node 1. And when a failback occurs, it takes 2.8 seconds for node 1 to take over the function of node 2.